Benang sari Melayu-Jawa - Noriah Mohamed (Institut Alam dan Tamadun Melayu, 2009)
Essays on social life and traditions of the Malay and Javanese people living in Malaysia
Keywords: Malays (Asian people); Javanese (Indonesian people)